Differential effects of warming and nitrogen fertilization on soil respiration and microbial dynamics in switchgrass croplands. Issue 8 (23rd April 2018) - Li, Jianwei; Jian, Siyang; de Koff, Jason P.; Lane, Chad S.; Wang, Gangsheng; Mayes, Melanie A.; Hui, Dafeng
Abstract: The mechanistic understanding of warming and nitrogen (N) fertilization, alone or in combination, on microbially mediated decomposition is limited. In this study, soil samples were collected from previously harvested switchgrass ( Panicum virgatum L.) plots that had been treated with high N fertilizer (HN: 67 kg N ha −1 ) and those that had received no N fertilizer (NN) over a 3‐year period. The samples were incubated for 180 days at 15 °C and 20 °C, during which heterotrophic respiration, δ 13 C of CO2, microbial biomass (MB), specific soil respiration rate (Rs : respiration per unit of microbial biomass), and exoenzyme activities were quantified at 10 different collections time. Employing switchgrass tissues (referred to as litter) with naturally abundant 13 C allowed us to partition CO2 respiration derived from soil and amended litter. Cumulative soil respiration increased significantly by 16.4% and 4.2% under warming and N fertilization, respectively. Respiration derived from soil was elevated significantly with warming, while oxidase, the agent for recalcitrant soil substrate decomposition, was not significantly affected by warming. Warming, however, significantly enhanced MB and Rs indicating a decrease in microbial growth efficiency (MGE). On the contrary, respiration derived from amended litter was elevated with N fertilization, which was consistent with the significantly elevated hydrolase. N fertilization, however, had little effect on MB and Rs, suggesting little change in microbial physiology. Temperature and N fertilization showed minimal interactive effects likely due to little differences in soil N availability between NN and HN samples, which is partly attributable to switchgrass biomass N accumulation (equivalent to 53% of fertilizer N). Overall, the differential individual effects of warming and N fertilization may be driven by physiological adaptation and stimulated exoenzyme kinetics, respectively. The study shed insights on distinct microbial acquisition of different substrates under global temperature increase and N enrichment.